Computational continuum mechanics of nanoscopic structures : nonlocal elasticity approaches /: nonlocal elasticity approaches. (2019) - Ghavanloo, Esmaeal; Rafii-Tabar, H (Hashem); Fazelzadeh, Seyed Ahmad
No abstract available